Use of A Comic Book to Assist Student Learning of Dimensions of Patient-Centered Care - Jagannath Muzumdar (University of Minnesota Libraries Publishing, 2016)
Objective: To evaluate the use of comic books as a supplemental reading to assist student learning of the dimensions of patient-centered care. The Innovation: A comic book titled Mom's Cancer was used as a supplemental reading in a course that introduced 2nd year pharmacy students (in a 0-6 year program) to the social aspects of pharmacy practice. Students read the book and provide their reflections about the book and topic covered in it. Critical Analysis: A total of 100 students registered in two sections of the course provided their responses. Student responses to the comic book activity were overwhelmingly positive. More than half of the student reflections included their personal experience with the healthcare system. The comic book format helped illustrate patient experiences with chronic illness to students. The range of comic books is not enough to give a comprehensive coverage of all the topics in the pharmacy curriculum. Getting the appropriate comic book for the respective topic could be challenging. Also, the effectiveness of comics as an education tool may be limited, if readers are less likely to take information provided via this medium seriously. Next Steps: The positive responses from students highlight the point that pharmacy faculty could use comic books in their pharmacy courses. Further research is needed to determine topics that would be effectively addressed by comic books and best practices for comic book use in pharmacy curriculum. Conflict of Interest The author declares no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties   Type: Note